﻿Toxares koreanus sp. nov. – a new Toxares species from South Korea (Hymenoptera, Braconidae, Aphidiinae) - Sangjin Kim; Željko Tomanović; Andjeljko Petrović; Jelisaveta Čkrkić; Gyeonghyoen Lee; Jongok Lim; Hyojoong Kim (Journal of Hymenoptera Research, 2022)
The genus Toxares Haliday, 1840 is a small taxon of Aphidiinae, consisting four valid species in the world. One Toxares species is recorded as new to science from South Korea, in this study. Descriptions and illustrations of the new species, T. koreanus sp. nov., are provided, together with their mitochondrial cytochrome c oxidase subunit I (COI) and D2 region of the nuclear gene for 28S rRNA (28S) sequences. The phylogenetic tree reconstructed using a combination of COI and 28S revealed the phylogenetic position of the genus Toxares within Aphidiinae.